Estilo y autoría en la información. Una aparente ausencia de identidad - Palau Sampio, Dolors (Estudios sobre el Mensaje Periodístico, 2009)
Journalistic articles are a reflection of different styles, different ways of seeing and constructing the reality that journalists produce. This paper proposes an analysis method to study newspaper articles in order to bring to light the linguistic mechanisms that reflect the point of view, the strategies that underlie the apparent absence of identity, an alleged authorship masked.